Case Report: A Rare Complication Following Catheter Ablation of Scar-Related Ventricular Tachycardia - Xu, Xiaoyong; Ye, Ming; Sun, Yaxun; Liu, Qiang; Ma, Fusheng; Jiang, Chenyang (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: The substrate for ventricular tachycardia (VT) in patients with structural heart disease is usually complex and often requires extensive ablation. As a result, the incidence of major procedure-related complications has been reported to be higher when compared to patients without structural heart disease. Here, we present a rare complication after extensive substrate modification of scar-related VT. CASE: A 65-year-old man with ischemic cardiomyopathy was referred to the electrophysiology laboratory for radiofrequency ablation of VT following repetitive implantable cardioverter-defibrillator shocks within a short period. As with hemodynamic intolerance of induced VT, an approach involving extensive endocardial substrate modification to reduce the arrhythmogenicity of the scars was adopted. After the procedure, the heart function of the patient deteriorated significantly. The postprocedural electrocardiogram showed a bizarre, extremely wide surface QRS complex (360 ms), termed homologous ventricular separation. The pronounced dyssynchrony of the ventricle was corrected by an upgrade to cardiac resynchronization therapy with defibrillation (CRT-D). As a result, the patient's symptoms improved significantly. The width of the intrinsic QRS complex was not recovered during an 18-month follow-up. CONCLUSION: Homologous ventricular separation is a rare arrhythmia, manifested as two separated QRS waves. This case report demonstrates, for the first time, that homologous ventricular separation may occur after extensive substrate modification of scar-related VT. CRT-D can correct the dyssynchronous ventricle caused by homologous ventricular separation.